Genotypic and phenotypic characteristics of Pseudomonas aeruginosa isolates associated with ulcerative keratitis - Winstanley, Craig; Kaye, Stephen B; Neal, Timothy J; Chilton, Helen J; Miksch, Silvia; Hart, C Anthony; the Microbiology Ophthalmic Group (Journal of Medical Microbiology, 2005)
A collection of 63 isolates of Pseudomonas aeruginosa associated with ulcerative keratitis, collected from six centres in England, were typed using serotyping and random amplified polymorphic DNA-PCR, and screened for several variable virulence-related genotypes and phenotypes. Sixty-one percent of the isolates were of either serotype O1 or serotype O11, but there was no evidence for a common clone. The majority of isolates (59 %) were PCR-positive for exoU rather than for exoS (38 %), and carried a-type fliC genes (76 %) rather than b-type (24 %). Isolates were PCR-positive for pyoverdine-receptor types at a prevalence of 38 % for type I, 46 % for type II and 8 % for type III. All but one of the isolates exhibited twitching activity. There was a correlation between the presence of exoS and twitching activity (P = 0.04), suggesting that a combination of exoS genotype and good twitching activity may have a role to play in ExoU-independent corneal virulence.